2019
DOI: 10.1111/dom.13672
|View full text |Cite
|
Sign up to set email alerts
|

Routine clinical use of liraglutide 3 mg for the treatment of obesity: Outcomes in non‐surgical and bariatric surgery patients

Abstract: thus be given the opportunity to show if they are "responders" at 16 weeks and "super responders" at 52 weeks; the medication would only be continued long-term in those who may benefit most. Future studies with liraglutide 3 mg and other obesity medications will have to assess long-term cost-effectiveness and the budgetary impact of using these medications to address not only body weight loss, but also the effects upon various obesity-related comorbidities. 15The strengths of our data include the large number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 17 publications
6
51
1
5
Order By: Relevance
“…14 Two further real-world studies have reported similar outcomes with liraglutide 3.0 mg. In the United Arab Emirates, median weight loss in 787 patients after ≥16-week treatment was 6.4% (6.0 kg), 15 and in Spain, mean weight loss in 100 patients over a median followup of 6.9 months was 7.7 kg 16 ; however, these studies did not assess outcomes by obesity class.…”
Section: Introductionmentioning
confidence: 99%
“…14 Two further real-world studies have reported similar outcomes with liraglutide 3.0 mg. In the United Arab Emirates, median weight loss in 787 patients after ≥16-week treatment was 6.4% (6.0 kg), 15 and in Spain, mean weight loss in 100 patients over a median followup of 6.9 months was 7.7 kg 16 ; however, these studies did not assess outcomes by obesity class.…”
Section: Introductionmentioning
confidence: 99%
“…There are few prospective trials investigating “rescue” pharmacotherapy with AOMs following bariatric surgery, with only six published to date with small numbers of patients (37‐43). One of the studies used an AOM which has since been withdrawn from the market, fenfluramine (40), and two other trials used AOMs after the adjustable laparoscopic gastric band, which is rarely used today (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The marked weight loss results achieved by the participants in the liraglutide study were likely confounded by diet, as the participants were instructed to achieve a 500 kcal/d deficit . The lone prospective study that investigated the effects of 3.0 mg of liraglutide reported that weight was reduced by 5.6% and 3.3% in RYGB and sleeve gastrectomy participants, respectively …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinical judgment is exercised when deciding which agent to prescribe. Some studies have been retrospective in nature and, for example, investigated the effects of liraglutide on weight loss outcomes; while one study noted the effects of sitagliptin after bariatric surgery, additional insight is needed …”
Section: Introductionmentioning
confidence: 99%